Clinical trial on the pharmacokinetics, pharmacodynamics and safety of tolvaptan in healthy Chinese males: an open-label, single and multiple dosage, parallel group study - Liu, Hongzhong; Liu, Tao; Liu, Ming; Zheng, Xin; Zhong, Wen; Zhao, Qian; Jiang, Ji; Hu, Pei; Li, Yishi (Frontiers in Pharmacology, 2025)
BackgroundTo determine the pharmacokinetics (PK), pharmacodynamics (PD) and safety of tolvaptan in healthy Chinese males.MethodsThree separate clinical trials were carried out on healthy Chinese males aged 18–45 years. Fifty received a single dose of tolvaptan of 7.5, 15, 30, 60 and 120 mg. In addition, 36 received multiple doses of 7.5, 30 and 60 mg once a day for 7 days. The primary outcomes measured were the PK parameters of tolvaptan and its two metabolites (DM-4103, DM-4107). Secondary endpoints included serum electrolytes, urine volume and water intake, which were monitored as pharmacological indicators. The safety profile was also evaluated in detail.ResultsAfter the administration of a single dose of tolvaptan, dose proportionality was observed for the area under the concentration-time curve (AUC) from 7.5 mg to 120 mg, but not for the maximum plasma concentration (Cmax). The mean (SD) values of Cmax from 7.5 mg to 120 mg were 69.8 (24.0), 102.0 (17.4), 245.5 (82.9), 323.9 (141.4), and 587.1 (364.0) ng/mL, respectively. Following multiple dose administration of 7.5, 30 and 60 mg tolvaptan once a day for 7 days, dose proportionality for the AUC was observed. The steady-state concentration was reached within 7 days of administration once a day. The accumulation ratios of AUCs were 1.2, 1.2 and 1.2 for the 7.5, 30 and 60 mg doses, respectively. Within the dosage range 7.5–120 mg, urine volume increased with dose after both single and multiple oral administrations of tolvaptan. No clinically significant changes in serum electrolytes (K+, Na+, Cl−, Mg2+) were detected following oral administration of 7.5 mg tolvaptan. The most common adverse events after single and multiple doses of tolvaptan were thirst, dry mouth and pharyngeal discomfort, which were known and predictable effects of tolvaptan.ConclusionTolvaptan demonstrated good tolerability and efficacy after single doses up to 120 mg and multiple doses up to 60 mg per day for 7 days. Dose proportionality was observed for AUC from 7.5 mg to 120 mg, but not for Cmax. Similar PK profiles were observed between single and multiple doses with slight accumulation.Clinical Trial Registrationhttps://clinicaltrials.gov/, identifier NCT07166796, NCT07166783 and NCT07166887.